Medicinal Use and Legalized Trade of Rhinoceros Horn From the Perspective of Traditional Chinese Medicine Practitioners in Hong Kong. (July 2018) - Cheung, Hubert; Mazerolle, Lorraine; Possingham, Hugh P.; Biggs, Duan
Rhino poaching in Africa has risen alarmingly over the last decade, driven by illegal trade and demand for horns in Asia, where it is used medicinally. Traditional Chinese medicine (TCM) has deep cultural roots, and understanding demand drivers will inform conservation decision-making. We interviewed 15 TCM practitioners in Hong Kong, investigating their familiarity with rhino horn, prescription experiences, and perspectives toward its use and trade. All interviewees believe that rhino horn possesses medicinal properties, despite general unfamiliarity with its chemical composition or any active ingredient. We compiled a list of 16 substitutes, finding that dosage adjustments produce equivalent treatment outcomes that compensate for potency differences. While most interviewees expressed support for trade legalization, most would prefer to continue prescribing substitutes. Further research into TCM stakeholder perspectives and preferences for rhino horn can inform conservation policy.